A celebration of historical Finnish women who wrote music, Part 1: Activists strive for gender equality - Susanna Välimäki; Nuppu Koivisto (Music Finland, 2022)
The history of Finnish music is unexpectedly rich in women who have written music. Nearly three dozen interesting personalities may be found in the 19th and early 20th centuries alone. The present article is an introduction to the research of this largely unexplored group of Finnish classical composers. The article is based on a book project Sävelten tyttäret: Säveltävät naiset Suomen historiassa 1700-luvun lopulta 1900-luvun alkuun [Daughters of music: Finnish Women Composers, from the late 18th to the early 20th centuries] by Susanna Välimäki and Nuppu Koivisto. The article also showcases a concert series given by violinist Mirka Malmi to give voice to this forgotten music by Finnish women composers.